Acute Phase Response as a Biological Mechanism‐of‐Action of (Nano)particle‐Induced Cardiovascular Disease. Issue 21 (29th March 2020) - Hadrup, Niels; Zhernovkov, Vadim; Jacobsen, Nicklas Raun; Voss, Carola; Strunz, Maximilian; Ansari, Meshal; Schiller, Herbert B.; Halappanavar, Sabina; Poulsen, Sarah S.; Kholodenko, Boris; Stoeger, Tobias; Saber, Anne Thoustrup; et al.
Abstract: Inhaled nanoparticles constitute a potential health hazard due to their size‐dependent lung deposition and large surface to mass ratio. Exposure to high levels contributes to the risk of developing respiratory and cardiovascular diseases, as well as of lung cancer. Particle‐induced acute phase response may be an important mechanism of action of particle‐induced cardiovascular disease. Here, the authors review new important scientific evidence showing causal relationships between inhalation of particle and nanomaterials, induction of acute phase response, and risk of cardiovascular disease. Particle‐induced acute phase response provides a means for risk assessment of particle‐induced cardiovascular disease and underscores cardiovascular disease as an occupational disease. Abstract : Cardiovascular disease is an important contributor to particle‐induced diseases. Inhalation of (nano)particles induces acute phase response, a known risk factor for cardiovascular disease. New evidence is reviewed, showing causal relationships between inhalation of particle and nanomaterials, induction of acute phase response and risk of cardiovascular disease. Particle‐induced acute phase response provides a means for risk assessment of particle‐induced cardiovascular disease.